Mechanisms of Anaerobic Soil Disinfestation: Volatile Fatty Acids Reduce Viability of Athelia (Sclerotium) rolfsii Sclerotia in Acidic Soil Conditions and Have Limited Effects on Endemic Trichoderma spp. - Swilling, Keagan J.; Shrestha, Utsala; Ownley, Bonnie H.; Gwinn, Kimberly D.; Butler, David M. (Frontiers in Sustainable Food Systems, 2021)
Volatile fatty acids (VFAs), such as acetic and n-butyric acid, released during anaerobic decomposition of organic soil amendments during anaerobic soil disinfestation (ASD) likely play a role in soilborne plant pathogen inoculum suppression. However, research is limited on the direct effects of soil VFA exposure on fungal plant pathogen inoculum, effects on pathogen antagonists such as Trichoderma spp., and the role of soil microbial VFA metabolism on reducing exposure effects. To address these limitations, a series of studies evaluated the effects of VFA (acetic or n-butyric acid), VFA concentration (4, 8, or 16 mmol/kg soil), soil sterilization by autoclaving, and soil amendment on the viability of Athelia rolfsii (Sclerotium rolfsii) sclerotia post VFA exposure, and soil populations of Trichoderma spp. HCl and water-only controls were included. After 4-days exposure in an acidic, anaerobic environment, sclerotial viability and colonization by culturable fungi or bacteria were assessed with standard procedures. Greenhouse experiments were similarly conducted to evaluate endemic soil populations of Trichoderma spp. following soil exposure to VFAs and Trichoderma spp. populations assessed with standard soil dilution plating onto semi-selective medium. Sclerotial germination was generally reduced by soil exposure to acetic (35.1% germination) or n-butyric (22.9% germination) acids compared to water (74.3% germination) and HCl (62.7% germination). Germination was reduced as VFA concentration increased from 4 to 8 and 16 mmol/kg (39.5%, 29.1% and 16.9%, respectively). In amended soils, there was no difference in sclerotial germination compared to non-amended soils, but in the greenhouse experiment there was a Trichoderma spp. population increase of over 300% in amended soil [3.4 × 106 colony forming units (CFU)/g soil] compared to the non-amended soil (9.6 × 105 CFU/g soil). Soil autoclaving had no effect on sclerotial germination at low VFA concentrations, but sclerotial germination was reduced at higher VFA concentrations compared to non-autoclaved soil. Our results suggest that VFAs contribute to sclerotial mortality in strongly acidic soil environments, and is influenced by VFA components and environment. Antifungal activity is less for acetic acid than for n-butyric, and less in non-sterile soil environments typical of field conditions than in sterile laboratory conditions.